Streaming Stigma and Acceptance: The Incongruent Representation of Mental Disorders and Neurodiversity in Indian Television and Over-the-Top (OTT) Media Series - Neha Singh; Rajni Mujral (Series. International journal of tv serial narratives)
Traditionally (in)famous for their grandeur, melodrama, and archetypical portrayal of family units, Indian soap operas have rarely represented neurodiversity and mental disorders sensitively. Barring a few OTTs and emergent productions that expose the Indian audience to globalised sensibilities, neurodivergent characters and those living with mental disorders are (mis)represented in all genres by either stigmatisation or romanticization. However, the on-screen portrayals of people living with psychiatric disorders oscillate between reinstating and demystifying the stereotypes, reflecting the vacillations of contemporary Indian society. Without undermining the practice of psychiatric diagnosis and cure, this paper locates mental illness and neurodiversity in the Indian context and studies their representations in select Hindi series of the 21st century, identifying predominant archetypes—the simpleton and the “psycho” criminal—that immensely influence the discourse surrounding atypical behaviour and thereby public perception.